2013
DOI: 10.1093/aje/kwt088
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diagnosed and Undiagnosed Type 2 Diabetes Mellitus Among US Adolescents: Results From the Continuous NHANES, 1999–2010

Abstract: Although prevalence and incidence of type 2 diabetes mellitus (T2DM) are reportedly increasing among adolescents, national data are lacking, particularly in regard to undiagnosed T2DM. To estimate the prevalence of diagnosed and undiagnosed T2DM among US adolescents, we analyzed a nationally representative cross-section of 11,888 adolescents aged 12-19 years who received a diabetes interview in the Continuous National Health and Nutrition Examination Survey during 1999-2010. Among them, a random subsample of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
94
3
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 29 publications
5
94
3
2
Order By: Relevance
“…The proportion of undiagnosed diabetes in the U.S. compares to that in Canada, ranging from one-fifth to onethird of total diabetes cases (6,18,32,33). For example, studies using the U.S. National Health Examination Survey have suggested that roughly one-third of the total diabetes prevalence is undiagnosed (30)(31)(32).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The proportion of undiagnosed diabetes in the U.S. compares to that in Canada, ranging from one-fifth to onethird of total diabetes cases (6,18,32,33). For example, studies using the U.S. National Health Examination Survey have suggested that roughly one-third of the total diabetes prevalence is undiagnosed (30)(31)(32).…”
Section: Discussionmentioning
confidence: 98%
“…For example, studies using the U.S. National Health Examination Survey have suggested that roughly one-third of the total diabetes prevalence is undiagnosed (30)(31)(32). Cowie et al (13) estimated the prevalence of diagnosed diabetes among U.S. adults in 1999-2002 to be 6.5%, with an additional 2.8% prevalence of undiagnosed diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable prevalence estimates for adolescents (15-19 years) in 2001 and 2009 were respectively 0.54 and 0.68 per 1000 (Dabelea et al 2014). Data from 1999 to 2010 NHANES, representative of US youth 12-19 years, indicated a total prevalence of T2DM of 0.36 per 1000 (Demmer et al 2013). This estimate combines diagnosed and undiagnosed cases of T2DM, with approximately 1/3 of the total being undiagnosed but having a fasting glucose level of ≥126 mg/dL (Demmer et al 2013).…”
Section: Prevalence and Incidence Of T2dm Related To Age Race And Ementioning
confidence: 93%
“…Data from 1999 to 2010 NHANES, representative of US youth 12-19 years, indicated a total prevalence of T2DM of 0.36 per 1000 (Demmer et al 2013). This estimate combines diagnosed and undiagnosed cases of T2DM, with approximately 1/3 of the total being undiagnosed but having a fasting glucose level of ≥126 mg/dL (Demmer et al 2013). The prevalence of pediatric T2DM is higher for females and among minorities in the USA (Dabelea et al 2014).…”
Section: Prevalence and Incidence Of T2dm Related To Age Race And Ementioning
confidence: 99%
“…
ОРИГИНАЛЬНЫЕ СТАТЬИ
49В последние годы метаболические нарушения рассматриваются как один из важных факторов риска развития сердечно-сосудистых заболеваний (ССЗ), связанных с атеросклерозом [1]. На фоне оптимального контроля таких важных факторов риска как гиперхолестеринемия и гипертония у лиц с ишемической болезнью сердца (ИБС), тем не менее, отмечается увеличение частоты сахарного диабета (СД) 2 типа [2].
…”
unclassified